Tissue-specific vascular endothelial signals and vector targeting, part B - Pasqualini, Renata (Advances in genetics, 2010)
The field of genetics is rapidly evolving, and new medical breakthroughs are occurring as a result of advances in knowledge gained from genetics research. This serial continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines. * Includes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines, providing researchers an overview and synthesis of the latest findings in the area * Presents up-to-date research from leaders in the field.